Acute intermittent porphyria: A case report with an unlisted HMBS gene variant (c.345–2A>C) - Julien Lerusse; Dominique Dive; François Charles Wang (Brain Disorders)
We report a case of acute intermittent porphyria in a 19-year-old patient, linked to an unlisted variant of the gene encoding hydroxymethylbilane synthase c.345–2A>C. Given the very low prevalence of porphyria in the general population, diagnosis is rarely made initially and may mainly mimic Guillain-Barré syndrome. Considering this, we provide an overview addressing various ways the disease manifests, paraclinical investigations, pathophysiology, and available therapeutic options. Specifically, human heme therapy in the case of acute crises is nearly unanimous in the literature. However, there is no consensus on the management between crises if the current first line choice treatment, namely givosiran, is not accessible. We report the clinical follow-up proposed for this patient.